RESTAURANT MANAGEMENT ADAPTATION DURING COVID-19: CASE OF RESTAURANTS IN SURABAYA - Gunawan, Steven; Indrianto, Agoes Tinus Lis (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Business is the purchase and sale of goods to make a profit. Restaurant businesses are two-way interactions involving service satisfaction and customer satisfaction, making it the most significant factor in restaurant sustainability. During this Covid-19 pandemic, Social distancing, curfew, and many kinds of government regulations push restaurant management and their teams to develop creative marketing. A conscious attempt to attune is the main point to survive and elevate for continuity of existence. This study will use textual analysis and qualitative data collection by analyzing location observation, personal interviews, and documentation based on current events focused on management's influence before and after the Covid-19 pandemic. Retrieval of data will be re-filtered and reviewed to display accurate data that has been regulated and valid. This research may have a recent incomplete implementation, but it can improve the current situation and conditions based on the restaurant business. Keywords: Restaurant, Business Management, Covid-19, and Adaptation.